Defect Detection and Cause Analysis of Steel Tube Tunnel in Storage Power Station. Issue 1 (February 2021) - Yuan, Ganglie; Wu, Peng; Che, Ailan
Abstract: Defects of draft tube such as void between steel liner and concrete will be formed for the influence of complex environment, resulting in the reduction of its bearing capacity. According to the characteristics of draft tube defects, a fast testing and evaluation method for draft tube structural defects was proposed combined with elastic wave imaging method. Taking the draft tube of a storage power station in Fujian Province as the research target, the field test was carried out using elastic wave test. Combined with waveform visualization and K-means clustering analysis method, the image recognition method was proposed, and defect types and distribution of the draft tube were obtained. Compared with results of the three-dimensional scanning, there is good consistency in the distribution of defects. An analysis was performed on the circumferentially coalescence area of the voids, and it is found that the load-bearing capacity of the draft tube in this area is reduced, the pressure it bears is greater than its own resistance, forming several cavities with large deformation.